2022
DOI: 10.1155/2022/7967722
|View full text |Cite|
|
Sign up to set email alerts
|

The RPL4P4 Pseudogene Is a Prognostic Biomarker and Is Associated with Immune Infiltration in Glioma

Abstract: Objective. Research over the past decade has suggested important roles for pseudogenes in gliomas. Our previous study found that the RPL4P4 pseudogene is highly expressed in gliomas. However, its biological function in gliomas remains unclear. Methods. In this study, we analyzed clinical data on patients with glioma obtained from The Cancer Genome Atlas (TCGA), the Chinese Glioma Genome Atlas (CGGA), the Genotype-Tissue Expression (GTEx), and the GEPIA2 databases. We used the R language for the main analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The current immunotherapies for personalized treatment continue to show limited effectiveness in enhancing the prognosis of advanced brain gliomas. The immune response processes are dynamically regulated by Macrophages 6 , Dendritic cells 7 , endothelial cells 8 , Inflammatory mediators, and extracellular matrix molecules 9 found in the tumor microenvironment. Hence, examining immune-related genes that influence the prognosis of glioma might unveil novel targets for immunotherapy targeting gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…The current immunotherapies for personalized treatment continue to show limited effectiveness in enhancing the prognosis of advanced brain gliomas. The immune response processes are dynamically regulated by Macrophages 6 , Dendritic cells 7 , endothelial cells 8 , Inflammatory mediators, and extracellular matrix molecules 9 found in the tumor microenvironment. Hence, examining immune-related genes that influence the prognosis of glioma might unveil novel targets for immunotherapy targeting gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%